Pendampingan Ibu-Ibu PKK Desa Sutapranan Dalam Pemanfaatan Lahan Kosong Melalui Budidaya Umbi Porang Yang Bernilai Ekonomi Tinggi - Pindha Kaptiningrum (LPPM Universitas Yudharta Pasuruan, 2020)
The land in Sutapranan village has a sufficient area and becomes a place of brick making. The former coal-making land can be used for other things such as porang cultivation. Porang as a plant of high economic value is very necessary to be cultivated in Sutapranan Village. Through the assistance of PKK, the land can be used as a place to cultivate porang tubers. This community service activity is done by doing ABCD method starting from data collection with observation and interview. The next step is to socialize the cultivation of porang to PKK and villagers, then the implementation of activities by planting and caring for porang tubers with PKK. The evaluation results carried out by the the community service team namely planting and maintaining porang activities have been carried out well and smoothly. For a month, porang tubers have grown to a height of one meter. To nurture porang, it's not complicated. By cleaning the weeds that grow around the porang is enough. Fertilization that is carried out periodically makes porang grow well. To harvest porang, it takes about a year from planting. The Community service Team also explained how to marketing and selling seeds obtained by harvest. Knowing how to marketing and a definite place of marketing, PKK are increasingly eager to continue the cultivation business for individuals and groups